2020
DOI: 10.3389/fnsyn.2020.00028
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Interacting Proteins With the Extracellular Loops of the Neuronal Glycoprotein M6a by TMT/MS

Abstract: Aparicio et al. TMT/MS Unveils Key M6a Interactors the surface of oligodendrocytes. Indeed, we demonstrated the (cis and trans) interaction between M6a and proteolipid protein (PLP) in neuroblastoma N2a cells. Finally, the 72 proteins were subjected to disease-associated genes and variants screening by DisGeNET. Apart from the diseases that have already been associated with M6a, most of the proteins are also involved in "autistic disorder," "epilepsy," and "seizures" increasing the spectrum of disorders in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 76 publications
1
10
0
Order By: Relevance
“…M6a was found within a complex of 30 interacting proteins, some of which are myelin sheath proteins, including the main myelin glycoproteins PLP and MAG; or are myelin sheath associated proteins like contactin 1 and contactin associated protein 1. In agreement, we identified 20 myelin proteins in the co-immunoprecipitation complexes formed by M6a's extracellular domains and rat hippocampal samples, in which PLP was experimentally confirmed (Aparicio et al, 2020). Also, Jahn et al (2020) identified M6a in the myelin sheath of post mortem human brains.…”
Section: M6a's Potential Role In Neuron-glia Interactionsupporting
confidence: 72%
See 4 more Smart Citations
“…M6a was found within a complex of 30 interacting proteins, some of which are myelin sheath proteins, including the main myelin glycoproteins PLP and MAG; or are myelin sheath associated proteins like contactin 1 and contactin associated protein 1. In agreement, we identified 20 myelin proteins in the co-immunoprecipitation complexes formed by M6a's extracellular domains and rat hippocampal samples, in which PLP was experimentally confirmed (Aparicio et al, 2020). Also, Jahn et al (2020) identified M6a in the myelin sheath of post mortem human brains.…”
Section: M6a's Potential Role In Neuron-glia Interactionsupporting
confidence: 72%
“…(C) We hypothesize that M6a function depends on its association with partner proteins in specific membrane microdomains. These associations, induce auto/phosphorylation in specific C-terminal residues facing the cytoplasm, and finally promote neuronal plasticity ( Fuchsova et al, 2009 ; Scorticati et al, 2011 ; Formoso et al, 2015a , b ; Garcia et al, 2017 ; Honda et al, 2017 ; Aparicio et al, 2020 ). For example, M6a can associate with extracellular matrix proteins such as brevican and tenascin C through its extracellular loops in trans and/or with cell adhesion proteins (NCAM and NPTN) through its extracellular domains in cis , triggering its phosphorylation and therefore the recruitment of adapter proteins (such as Rap) and the activation of protein kinases that finally promote the reorganization of the cytoskeleton.…”
Section: Gene Protein and Structural Domainsmentioning
confidence: 99%
See 3 more Smart Citations